2015
DOI: 10.1002/jcad.12029
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors' Ways of Knowing and Social Orientation in Relationship to Poverty Beliefs

Abstract: The beliefs about poverty, ways of knowing, and social relationship orientation of 513 American School Counselor Association members were evaluated using canonical correlation analysis. Results indicated a relationship between the beliefs that poverty is caused by individuals' internal characteristics, connected knowing, and social hierarchies. A relationship also exists for school counselors who believe that poverty is caused by external factors, use a combination of connected and separate knowing, and embrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 59 publications
3
18
1
Order By: Relevance
“…Bullock (2013) identified individualism as one of the core tenets in American Society for explaining socioeconomic differences. This is consistent with prior research, which found substantial correlations between individualism and internal attributions of poverty (Bray & Schommer-Aikins, 2015;Bullock, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Bullock (2013) identified individualism as one of the core tenets in American Society for explaining socioeconomic differences. This is consistent with prior research, which found substantial correlations between individualism and internal attributions of poverty (Bray & Schommer-Aikins, 2015;Bullock, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…The authors of the current study previously examined attributions for poverty, epistemological beliefs, and social relational views in a population of currently practicing school counselors (Bray & Schommer-Aikins, 2015). The researchers found a relationship among school counselor's endorsement of a vertical hierarchical social structure, the use of separate knowing, less multicultural training, and the endorsement of the idea the internal characteristics of the person cause poverty.…”
Section: Undergraduate Students Attributions About Povertymentioning
confidence: 92%
“…A total of 388 participants started the survey (8.7% rate of starting the survey), and 333 participants completed the survey (7.5% usable response rate). This response rate was lower than other studies using similar methods (e.g., Harris, ; Mullen & Gutierrez, ) but higher than other research (e.g., Bray & Schommer‐Aikins, ; Mullen, Lambie, Griffith, & Sherrell, ).…”
Section: Methodscontrasting
confidence: 71%
“…Furthermore, there is a lack of knowledge of how demographic variables (e.g., age, gender, ethnocultural identity, personal and professional exposure to poverty, counseling specialty) may influence that relationship. Previous research indicates a significant link between higher levels of MCC and increased multicultural training (Bray & Schommer-Aikins, 2015); thus, if MCC and poverty beliefs can be shown as significantly linked, increased multicultural training could be considered facilitative of both MCC in general and positive poverty beliefs more specifically. It is theoretically expected that MCC and poverty beliefs are related (e.g., Bray & Schommer-Aikins, 2015;Toporek & Pope-Davis, 2005).…”
mentioning
confidence: 99%
“…It is theoretically expected that MCC and poverty beliefs are related (e.g., Bray & Schommer‐Aikins, ; Toporek & Pope‐Davis, ). Previous research has found a significant relationship between MCC and poverty beliefs, although each study is limited to one counseling specialty (Bray & Schommer‐Aikins, ) or level of counseling experience (Toporek & Pope‐Davis, ). In contrast, the present study used a sample of counselors of various specialties.…”
mentioning
confidence: 99%